2022
DOI: 10.3390/genes13081306
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Parkinson’s Disease Genes and Role of PARK2 in Amyotrophic Lateral Sclerosis: An NGS Study

Abstract: Amyotrophic lateral sclerosis (ALS) and Alzheimer’s disease (AD) patients show a higher prevalence of Lewy body disease than the general population. Additionally, parkinsonian features were found in about 30% of ALS patients. We aimed to explore the frequency of Parkinson’s disease (PD)-causative genes in ALS patients, compared to AD and healthy controls (HCs). We used next-generation sequencing multigene panels by analyzing SNCA, LRRK2, PINK1, PARK2, PARK7, SYNJ1, CHCHD2, PLA2G6, GCH1, ATP13A2, DNAJC6 and FBX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…Recent genetic studies have taken the considerable overlap of clinical and pathological features of PD, ALS, and MSA into account, and have highlighted the importance of testing known pathological genetic mutations across these neurodegenerative diseases [ 141 , 142 , 143 ]. Collectively, these studies found no association between PD-related SNCA variants and ALS, however, their analyses focused on SNP-based risk association, and it has been previously shown that only ~8% of heritability in ALS is associated with genome-wide SNPs [ 144 ].…”
Section: Is Amyotrophic Lateral Sclerosis a Synucleinopathy?mentioning
confidence: 99%
“…Recent genetic studies have taken the considerable overlap of clinical and pathological features of PD, ALS, and MSA into account, and have highlighted the importance of testing known pathological genetic mutations across these neurodegenerative diseases [ 141 , 142 , 143 ]. Collectively, these studies found no association between PD-related SNCA variants and ALS, however, their analyses focused on SNP-based risk association, and it has been previously shown that only ~8% of heritability in ALS is associated with genome-wide SNPs [ 144 ].…”
Section: Is Amyotrophic Lateral Sclerosis a Synucleinopathy?mentioning
confidence: 99%
“…ALS patients exhibit a higher prevalence of Lewy body disease and 30% of ALS patients present parkinsonian features. PD-causative genes have therefore been proposed as risk modifiers in ALS and a higher frequency of mutations in autosomal recessive PD genes has been reported in the ALS versus control cohort [31]. The genetic link between ATP13A2 and ALS is however not solid, and is mainly based on a report describing a patient carrying a homozygous truncation variant in ATP13A2 (among variants in more than 25 other genes) [4].…”
Section: Discussionmentioning
confidence: 99%
“…We found that this variant had only a modest impact on spermine uptake in cells (a of approximately 20%), while the ATPase activity in microsomes was not affected, questioning whether this variant may be diseasecausing. Four more variants in ATP13A2 have recently been identified in a cohort of 330 ALS patients, but detailed clinical and allele information is lacking [31]. Of these, the A461Vfs*5 variant is most likely disruptive, but was identified in a patient with disease onset at the age of 87.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This overlap in pathological features has led to the recognition of a new pathological entity known as TDP-43 proteinopathy, which is characterized by the accumulation of abnormal TDP-43 protein in the brain and spinal cord. TDP-43 proteinopathy has been identified in both ALS and FTD patients, suggesting that they may share a common underlying pathology (7).…”
Section: Pathological Featuresmentioning
confidence: 99%